Development of Creative Competence in Teaching Future Teachers of Fine Arts to Work in Graphic Materials - Ulfat Shuhratovich, Ismatov; Sarvar Tursunmurotovich, Sabirov (International Journal of Psychosocial Rehabilitation, 2020)
Higher education consists of the development of future teachers of fine arts studying in the direction of "fine arts": pencil drawing, various graphic materials in painting lessons; work on pencils, sanguine, ink, coal, tempera, sauce, ballpoint pens, and markers; study of the specific aspects and techniques of each material; assistance in finding a way of their own creativity; and development of creative compositions.